Impacts of emergency health protection measures upon air quality, traffic and public health: evidence from Oxford, UK. (15th January 2022) - Singh, Ajit; Bartington, Suzanne E.; Song, Congbo; Ghaffarpasand, Omid; Kraftl, Martin; Shi, Zongbo; Pope, Francis D.; Stacey, Brian; Hall, James; Thomas, G. Neil; Bloss, William J.; Leach, Felix C.P.
Abstract: Emergency responses to the COVID-19 pandemic led to major changes in travel behaviours and economic activities in 2020. Machine learning provides a reliable approach for assessing the contribution of these changes to air quality. This study investigates impacts of health protection measures upon air pollution and traffic emissions and estimates health and economic impacts arising from these changes during two national 'lockdown' periods in Oxford, UK. Air quality improvements were most marked during the first lockdown with reductions in observed NO2 concentrations of 38% (SD ± 24.0%) at roadside and 17% (SD ± 5.4%) at urban background locations. Observed changes in PM2.5, PM10 and O3 concentrations were not significant during first or second lockdown. Deweathering and detrending analyses revealed a 22% (SD ± 4.4%) reduction in roadside NO2 and 2% (SD ± 7.1%) at urban background with no significant changes in the second lockdown. Deweathered-detrended PM2.5 and O3 concentration changes were not significant, but PM10 increased in the second lockdown only. City centre traffic volume reduced by 69% and 38% in the first and second lockdown periods. Buses and passenger cars were the major contributors to NO2 emissions, with relative reductions of 56% and 77% respectively during the first lockdown, and less pronounced changes in the second lockdown. While car and bus NO2 emissions decreased during both lockdown periods, the overall contribution from buses increased relative to cars in the second lockdown. Sustained NO2 emissions reduction consistent with the first lockdown could prevent 48 lost life-years among the city population, with economic benefits of up to £2.5 million. Our findings highlight the critical importance of decoupling emissions changes from meteorological influences to avoid overestimation of lockdown impacts and indicate targeted emissions control measures will be the most effective strategy for achieving air quality and public health benefits in this setting. Graphical abstract: Image 1 Highlights: Roadside NO2 concentrations reduced by 22% in the first lockdown period only. NO2 emissions from buses and cars reduced by 56% and 77% during the first lockdown. PM10 concentrations increased signficantly during the second lockdown only. Lockdown related NO2 reductions could save 48 life-years and up to £2.5 million. Targeted emissions control measures are needed to deliver public health benefits.